Sifat Kimia dan Sensori Teh Celup Cascara Stevia dengan Metode Pengeringan Kulit Kopi dan Persentase Gula Stevia (Stevia rebaudiana Bertoni) yang Berbeda - Murlida, Eva; NIlda, Cut; Safriani, Novi; Aliansyah, Aliansyah (Agriculture Faculty, 2024)
Cascara is a dry tea made from coffee husk waste. Cascara is prepared in the shape of dip packets to make it easier for customers, and stevia (Stevia rebaudiana Bertoni) is added since consumers like sweet drinks and to promote consumer preference. The purpose of this study is to investigate the influence of the coffee skin drying process and cascara and stevia ratio on the physicochemical and sensory qualities of cascara tea bags. This research used a factorial completely randomized design where the first factor is the drying method, and the second is the percentage of added stevia. The research data obtained is then analyzed using Analysis of Variance (ANOVA) and followed with Duncan's Multiple Range Test (DMRT) if there are differences between treatments. The drying technique treatment variance influenced pH, total dissolved solids, and color hedonic. The research revealed that the pH of cascara dried in the oven was higher than that of sun drying, while the total soluble solids of sun drying were higher than that of oven drying. The pH and total soluble solids increased as the proportion of stevia added increased. The hedonic test mean result for fragrance was 3.49 (neutral), color was 3.47 (neutral), and taste was 3.13 (neutral). The cascara scent description test had a mean value of 2.74 (neutral), a cascara color description of 2.74 (light), a sweet taste description of 2.81 (neutral), a sour taste description of 2.24 (weak), a bitter taste description of 1.81 (weak), and an astringent taste description of 2.24 (weak). The total phenols value in sun drying with a 20% stevia addition yielded 139 mg GAE/mL